Lo Batèu de pèira : contar sa vida ò veire dins la nuèch - Danièle Julien (Revue des Langues Romanes)
The article analyses with the tools of psychocriticism the particularities of the autobiography-inspired narrative as they appear in the novel. The presence of death is particularly highlighted. Emphasis is placed on the philosophical reflection that accompanies the recounting of everyday events, from the most “banal” to the most tragic, and on the time of childhood, with its fears and anxieties, which continually weighs on the human being once he has become an adult.